-3(u+2)=-3(6u-1)+3u

Simple and best practice solution for -3(u+2)=-3(6u-1)+3u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(u+2)=-3(6u-1)+3u equation:



-3(u+2)=-3(6u-1)+3u
We move all terms to the left:
-3(u+2)-(-3(6u-1)+3u)=0
We multiply parentheses
-3u-(-3(6u-1)+3u)-6=0
We calculate terms in parentheses: -(-3(6u-1)+3u), so:
-3(6u-1)+3u
We add all the numbers together, and all the variables
3u-3(6u-1)
We multiply parentheses
3u-18u+3
We add all the numbers together, and all the variables
-15u+3
Back to the equation:
-(-15u+3)
We get rid of parentheses
-3u+15u-3-6=0
We add all the numbers together, and all the variables
12u-9=0
We move all terms containing u to the left, all other terms to the right
12u=9
u=9/12
u=3/4

See similar equations:

| 5(2^n–2)=5(2^3n+10) | | 3500-26x=3929-37x | | -2(x+7)=x-2+2(6x+3) | | -4(-7y+4)-4y=6(y-1)-1 | | (5b-9)-2(2b+2)=-7 | | 4.8p+3.6+4.7-2.83=5.2+3.9p | | 31/2a+3=3 | | y/3-2=6 | | 5014x^2+58x-30=1 | | y3-2=6 | | 6m=14m- | | 4a-7=-6a- | | 150=300-5s | | x*0.5^x=10^-8 | | 2x+5x=2+5 | | 12/15÷x=11 | | 2(x-2)=2x+6-4(-3x-2) | | 162-w=259 | | -16X+8y=-8 | | 45-k=28 | | 27=3x+5 | | 1/2(13)h=100.75 | | 9(x-1)^2=16 | | 12+m/3=5 | | -4=12-8x | | 128=16t^2+64t-48 | | -6n-11=25 | | x+-8=1 | | 33/2+3y/5=7y/10 | | 4r*4r+48=4r+24+4r*4r-8r | | 2x-46=100 | | -4(5+8k)=6(3k+5) |

Equations solver categories